(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2012)
Recensión de la obra: KÜHNHARDT, Ludger (2009). Crises in European Integration. Challenges and Responses, 1945-2005. New York, Oxford: Berghahn Books.